2022
DOI: 10.3390/ijms231911350
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Mitochondrial Function Is Essential in the Endothelium-Dependent Vasodilation Induced by Acacetin in Hypertensive Rats

Abstract: Mitochondrial dysfunction in the endothelium contributes to the progression of hypertension and plays an obligatory role in modulating vascular tone. Acacetin is a natural flavonoid compound that has been shown to possess multiple beneficial effects, including vasodilatation. However, whether acacetin could improve endothelial function in hypertension by protecting against mitochondria-dependent apoptosis remains to be determined. The mean arterial pressure (MAP) in Wistar Kyoto (WKY) rats, spontaneously hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Xanthohumol, another flavone, has been reported to upregulate mitofusin 2, a mitochondrial profusion factor, to alleviate murine neuronal death in nervous system diseases [39]. Similarly, while hypertension can be spawned by reduced mitochondria fusion, flavonoids have been shown to reverse Angiotensin II-dependent increases in dynamin-related protein 1 (profission) and decreases in optic atrophy 1 (profusion) [40]. These mitochondrial structural changes may have functional impacts on flavone-mediated hypertension.…”
Section: Flavones Affect Mitochondrial Biogenesis Dynamics and Energe...mentioning
confidence: 99%
“…Xanthohumol, another flavone, has been reported to upregulate mitofusin 2, a mitochondrial profusion factor, to alleviate murine neuronal death in nervous system diseases [39]. Similarly, while hypertension can be spawned by reduced mitochondria fusion, flavonoids have been shown to reverse Angiotensin II-dependent increases in dynamin-related protein 1 (profission) and decreases in optic atrophy 1 (profusion) [40]. These mitochondrial structural changes may have functional impacts on flavone-mediated hypertension.…”
Section: Flavones Affect Mitochondrial Biogenesis Dynamics and Energe...mentioning
confidence: 99%
“…Research has demonstrated that hypertension induces mitochondrial dysfunction in vascular endothelial and smooth muscle cells, elevating reactive oxygen species generation (Dikalova et al, 2010). Dynamics-related protein 1 (DRP1) activation and optic atrophy protein 1 (OPA1) downregulation impairs mitochondrial dynamics in the small mesenteric arteries of SHRs, leading to an increase in mtROS emission, inflammation, and growth factor signaling, which causes medial thickening and luminal constriction (Li et al, 2022a). Vascular mitochondrial dysfunction can stimulate proliferation and phenotypic switching from contractile to proliferative in vascular smooth muscle cells (VSMCs), resulting in vascular remodeling and stiffness (Lu et al, 2021;Ye et al, 2021).…”
Section: Vesselsmentioning
confidence: 99%
“…Icariin (ICA) is a flavonol glycoside derived from the Chinese medicinal herb Epimedium. It has been used to treat hypertension, Alzheimer's disease, cerebral ischemia, and depression (Li et al, 2022a). Qian et al observed that ICA had a protective effect on cardiac remodeling in SHRs and that oral administration of ICA (20 and 40 mg/kg/day) prevented apoptosis of cardiomyocytes and improved left ventricular remodeling and mitochondrial abnormalities.…”
Section: Flavonoidsmentioning
confidence: 99%